2014
DOI: 10.1037/a0035935
|View full text |Cite
|
Sign up to set email alerts
|

A contextual approach to experiential avoidance and social anxiety: Evidence from an experimental interaction and daily interactions of people with social anxiety disorder.

Abstract: Experiential avoidance, the tendency to avoid internal, unwanted thoughts and feelings, is hypothesized to be a risk factor for social anxiety. Existing studies of experiential avoidance rely on trait measures with minimal contextual consideration. In two studies, we examined the association between experiential avoidance and anxiety within real-world social interactions. In the first study, we examined the effect of experiential avoidance on social anxiety in everyday life. For two weeks, 37 participants with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
121
1
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(139 citation statements)
references
References 73 publications
11
121
1
6
Order By: Relevance
“…This increased use of experiential avoidance may be problematic as previous findings have linked experiential avoidance to heightened measures of psychopathology and poor positive affect (e.g., Hayes et al, 2004, Kashdan, Barrios, Forsyth, & Steger, 2006. Specifically, it has previously been established that experiential avoidance precedes symptoms of social anxiety (Kashdan et al, 2014). Concerning positive affect, HSAs experienced less positive affect in this study as has been consistently demonstrated in the literature (e.g., Kashdan, 2007;Kashdan et al, 2011).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…This increased use of experiential avoidance may be problematic as previous findings have linked experiential avoidance to heightened measures of psychopathology and poor positive affect (e.g., Hayes et al, 2004, Kashdan, Barrios, Forsyth, & Steger, 2006. Specifically, it has previously been established that experiential avoidance precedes symptoms of social anxiety (Kashdan et al, 2014). Concerning positive affect, HSAs experienced less positive affect in this study as has been consistently demonstrated in the literature (e.g., Kashdan, 2007;Kashdan et al, 2011).…”
Section: Discussionsupporting
confidence: 51%
“…For instance, in an experience sample study, Kashdan et al (2014) found that momentary experiential avoidance was more strongly associated with anxiety during social interactions for individuals with EMOTION REGULATION FLEXIBILITY IN SAD 4 SAD than for healthy controls. Moreover, they found that greater experiential avoidance during a self-disclosure conversation temporally preceded social anxiety symptoms over the remainder of the conversation.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Theorists contend, and empirical and experimental research has found, that EA is especially pertinent to the development and maintenance of social anxiety in particular (Heimberg et al 2010;Kashdan et al , 2011Kashdan et al , 2013Kashdan et al , 2014. Heimberg et al (2010) theorize, with supporting studies, that an emotion regulation strategy used by socially anxious individuals is deliberately inhibiting the expression of emotions in interpersonal situations (i.e., expressive suppression).…”
mentioning
confidence: 96%
“…O processo de evitação fornece alívio imediato, entretanto essa sensação prazerosa é temporária. Estudos mostram que o uso constante dessa forma de regulação emocional tende a aumentar as sensações negativas em vez de reduzi-las, com isso, a tentativa de evitar sentimentos e pensamentos de rejeição acaba amplificando esses sentimentos e, assim, aumentando a ansiedade sentida (Kashdan et al, 2014). Além disso, em função da utilização da estratégia disfuncional da evitação e da evitação do enfrentamento, hipotetiza-se que, ao longo do tempo, a estratégia de escapar das situações torna-se frequente, independentemente de a situação ser aversiva ou não (Kashdan, Barrios, Forsyth, & Steger, 2006).…”
Section: Transtorno De Ansiedade Socialunclassified
“…Outro dado interessante foi o fato de que em situações em que eram alvo de críticas, a evitação foi menos utilizada mesmo com níveis elevados de ansiedade, já quando a situação era menos ansiogênica, as pessoas que utilizavam mais estratégias de evitação apresentaram índices maiores de ansiedade (Kashdan et al, 2014).…”
Section: Transtorno De Ansiedade Socialunclassified